2018
DOI: 10.1002/marc.201800069
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐Crosslinked Amorphous Polysaccharide Hydrogels Based on Chitosan/Alginate for Wound Healing Applications

Abstract: Development of advanced wound dressing materials with rapid healing rates is in urgent demand for wound cares. A suitable microenvironment will promote cell proliferation and migration, which benefits to early wound healing and prevents inflammations and scars. In this work, N-carboxymethyl chitosan- and alginate-based hydrogels are prepared via both electrostatic interaction and divalent chelation with epidermal growth factor (EGF) payload to promote the cell proliferation and wound healing. The dual-crosslin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(71 citation statements)
references
References 44 publications
0
71
0
Order By: Relevance
“…It has been well accepted that modern wound dressings offer a more effective alternative to traditional dressings. Table 1 lists the characteristic of commercialized modern wound dressings including hydrocolloids, hydrogels, alginates [48], sponges and transparent films [49]. Importantly, their advantages, disadvantages and application ranges have been outlined.…”
Section: Current Commercial Wound Dressing Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well accepted that modern wound dressings offer a more effective alternative to traditional dressings. Table 1 lists the characteristic of commercialized modern wound dressings including hydrocolloids, hydrogels, alginates [48], sponges and transparent films [49]. Importantly, their advantages, disadvantages and application ranges have been outlined.…”
Section: Current Commercial Wound Dressing Materialsmentioning
confidence: 99%
“…Typically, radially aligned fibrous membranes were developed readily by making use of collector composed of a ring electrode and a metal pin [72]. Xia et al [73] demonstrated that dural fibroblasts were able to stretch Infected wounds [48] along nanofibers, and their migration toward the center of nanofiber mat was enhanced along with a regular arrangement of ECM such as collagen I (Fig. 1c).…”
Section: D Nanofibrous Membranesmentioning
confidence: 99%
“…In recent years, the development of multifunctional antibacterial materials with hemostasis and wound‐healing capabilities has attracted increasing attention in the field of biomaterials . The chlorhexidine diacetate (CHX)‐loaded nanogels (CLN) were first prepared via enzyme degradation procedure, and the obtained CLNs were mixed with precursors of aminoethyl methacrylate hyaluronic acid (HA‐AEMA) and methacrylated methoxy polyethylene glycol (mPEG‐MA) for photoinduced cross‐linking ( Figure a) .…”
Section: Biodegradable Polymeric Nanosystems Containing Antibioticsmentioning
confidence: 99%
“…Alginate has shown effectiveness as a constituent of acellular matrix skin grafts to reduce wound healing duration, which is especially poor with diabetic patients [131][132][133]. A large multicenter study involving 75 patients with 100 wounds (50% UT grade 3 wounds) was conducted using an alginate containing GraftJacket ® matrix skin graft.…”
Section: Wound Healing Treatmentmentioning
confidence: 99%